Research on online social media marketing strategies of traditional consumer brands: A case study of Mac cosmetics - Yan Weixi (SHS Web of Conferences)
This paper explores the impact of social media on the marketing strategies of traditional consumer brands, focusing on MAC Cosmetics. Nowadays, social media is vital for businesses to engage customers and enhance their online presence. This study examines how MAC Cosmetics utilizes platforms like Instagram, Facebook, and Twitter to boost brand visibility, foster customer interaction, and drive sales. Through literature review and case study analysis, it identifies key strategies such as targeted advertising, influencer collaborations, and user-generated content. The findings highlight social media’s significant role in influencing consumer behaviour and enabling direct brand-audience communication. The study also discusses the challenges and opportunities in social media marketing, providing insights for traditional brands to leverage social media for enhanced marketing outcomes. The conclusions emphasize the necessity for a well-integrated social media strategy to remain competitive in the evolving digital landscape, contributing to a deeper understanding of the intersection between traditional brand marketing and social media dynamics.